Cisplatin-Resistant Gastric Cancer Cells Promote the Chemoresistance of Cisplatin-Sensitive Cells via the Exosomal RPS3-Mediated PI3K-Akt-Cofilin-1 Signaling Axis - Sun, Meng-Yao; Xu, Bo; Wu, Qiu-Xue; Chen, Wen-Lian; Cai, Si; Zhang, Hui; Tang, Qing-Feng (Frontiers in Cell and Developmental Biology, 2021)
Cisplatin is an important agent in first-line chemotherapy against gastric cancer (GC). However, consequential drug resistance limits its effectiveness for the treatment of GC. In this study, a cisplatin resistant gastric cancer cell line SGC7901R was determined by LC-MS/MS with increased exosomal levels of RPS3 protein. SGC7901R cell derived exosomes were readily taken up by cisplatin sensitive SGC7901S cells, thus triggering off a phenotype of chemoresistance in the receptor cells. Subsequently, it was demonstrated that exosomal RPS3 was essential for inducing chemoresistance of receptor cells as shown by the acquisition of this phenotype in SGC7901S cells with enforced expression of RPS3. Further mechanism study demonstrated that cisplatin‑resistant gastric cancer cells-derived exosomal RPS3 enhanced the chemoresistance of cisplatin‑sensitive gastric cancer cells through the PI3K-Akt-cofilin-1 signaling pathway. All these findings demonstrated that cisplatin resistant gastric cancer cells communicate with sensitive cells through the intercellular delivery of exosomal RPS3 and activation of the PI3K-Akt-cofilin-1 signaling pathway. Targeting exosomal RPS3 protein in cisplatin resistant gastric cancer cells may thus be a promising strategy to overcome cisplatin resistance in gastric cancer.